2018
DOI: 10.1016/j.ijrobp.2018.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Objective Evaluation of a Didactic Curriculum for the Radiation Oncology Medical Student Clerkship

Abstract: Objective evaluation of a structured didactic curriculum for the radiation oncology clerkship at early and late time points demonstrated significant improvement in radiation oncology knowledge. Students who completed clerkships at ROECSG institutions performed objectively better than students who completed clerkships at non-ROECSG institutions. These results support including a structured didactic curriculum as a standard component of the radiation oncology clerkship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Considering this finding, the number of faculties offering a complete RO rotation (70.8%) for final-year medical students should be increased. It is noteworthy that structured didactic sessions for clerkships could improve both students' knowledge and interest in the field, but also lead to better evaluation results [22][23][24][25], and should therefore be considered for the RO rotations in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this finding, the number of faculties offering a complete RO rotation (70.8%) for final-year medical students should be increased. It is noteworthy that structured didactic sessions for clerkships could improve both students' knowledge and interest in the field, but also lead to better evaluation results [22][23][24][25], and should therefore be considered for the RO rotations in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that RO education was even more limited than medical oncology education [8] . Besides, the lack of a mandatory clerkship in RO hinders a practical approach to RO [25] .…”
Section: Discussionmentioning
confidence: 99%
“…These observations should stimulate a bigger effort to broaden the visibility of RO. Local and multi-institutional pilot initiatives were undertaken to include RO into the core curriculum for medical students [6] , [8] , [9] , [12] , [14] , [17] , [25] , [26] . These initiatives paralleled similar processes implemented for medical students in other medical disciplines such as internal medicine [27] , surgery [28] , emergency medicine [29] , dermatology [30] , uro-nephrology [31] , [32] , palliative care medicine [33] , radiology [20] and nuclear medicine [34] .…”
Section: Discussionmentioning
confidence: 99%
“…27 These combined sessions significantly improved test averages by 43% (P < 0.001) and 11% (P < 0.05) respectively as well as increased basic knowledge of dermatologic cancers. 28,29 Liu et al did not observe this with more advanced topics such as staging. 30 This trend continues with holistic care lectures and small group discussions.…”
mentioning
confidence: 95%